High diversity of Cryptosporidium subgenotypes identified in Malaysian HIV/AIDS individuals targeting gp60 gene - Iqbal, Asma; Lim, Yvonne Ai Lian; Surin, Johari; Sim, Benedict Lim Heng (Public Library of Science, 2012)
Background: Currently, there is a lack of vital information in the genetic makeup of Cryptosporidium especially in developing countries. The present study aimed at determining the genotypes and subgenotypes of Cryptosporidium in hospitalized Malaysian human immunodeficiency virus (HIV) positive patients.